β1 integrins with individually disrupted cytoplasmic NPxY motifs are embryonic lethal but partially active in epidermis - Meves, Alexander (J Invest Dermatol, 2013)
β1 integrin adhesion is believed to require binding of talins and kindlins to the membrane proximal and distal NPxY motifs of the β1 cytoplasmic tail, respectively. To test this hypothesis we substituted the membrane proximal and distal tyrosines (Y) of the β1 tail with alanine (A) residues (β1 Y783A; β1 Y795A) in the germline of mice. We report that β1 Y783A or β1 Y795A substitutions blocked talin or kindlin binding, respectively, and led to β1 null-like peri-implantation lethality. Expression of β1 Y783A or β1 Y795A in the epidermis, however, resulted in skin blister and hair follicle phenotypes that were considerably milder than those observed with β1 integrin gene deletion or a β1 double Y-to-A substitution (β1 YY783/795AA). In culture, defects in adhesion, spreading and migration were more severe with the β1 Y783A than with the β1 Y795A substitution despite markedly reduced β1 Y795A integrin surface levels due to diminished protein stability. We conclude that regulation of β1 integrin adhesion through talins and kindlins may differ substantially between stably adherent keratinocytes and cells of the developing embryo and that β1 cytoplasmic NPxY motifs contribute individually and independent of each other to β1 function in keratinocytes.